Interest in Behavioral and Psychological Treatments Delivered Face-to-Face, by Telephone and by Internet - Mohr, David C. (2010)
BACKGROUND: Little is known about the acceptability of internet and telephone treatments, or what factors might influence patient interest in receiving treatments via these media. PURPOSE: This study examined the level of interest in face-to-face, telephone and internet treatment, and factors that might influence that interest. METHODS: 658 primary care patients were surveyed. RESULTS: Among patients interested in some form of behavioral treatment, 91.9% were interested or would consider face-to-face care, compared to 62.1% for telephone and 48.3% for internet care. Symptom severity was unrelated to interest in treatment delivery medium. Interest in specific treatment targeting mental health, lifestyle or pain was more strongly predictive of interest in face-to-face treatment than telephone or internet treatments. Only interest in lifestyle intervention was predictive of interest in internet delivered treatment. Time Constraints as a barrier was more predictive of interest in telephone and internet treatments, compared to face-to-face. CONCLUSIONS: These findings provide some support for the notion that telephone and internet treatments may overcome barriers. People who seek help with lifestyle change may be more open to internet delivered treatments while interest in internet intervention does not appear to be associated with the desire for help in mental health, pain or tobacco use.